2014
DOI: 10.11564/28-0-568
|View full text |Cite
|
Sign up to set email alerts
|

Place Matters: Community Level Effects of Women’s Autonomy on Ethiopian Children’s Immunization Status

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This may be because social interactions in Ethiopia are often intertwined and therefore, the effect of group group-level autonomy on individual behavior may exceed the individual’s autonomy [ 30 ]. The group level may indicate that even though Ethiopian women have low decision-making power, living in a strong decision-making society for women can lead to increased use of shared information and resources and ultimately, help improve the quality of life for women and their family members as well [ 18 ]. Female decision-making power at the group level had a beneficial effect on lowering the risk of anemia, implying that gender disparity, as measured by low decision-making power, may influence the development of anemia among married women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because social interactions in Ethiopia are often intertwined and therefore, the effect of group group-level autonomy on individual behavior may exceed the individual’s autonomy [ 30 ]. The group level may indicate that even though Ethiopian women have low decision-making power, living in a strong decision-making society for women can lead to increased use of shared information and resources and ultimately, help improve the quality of life for women and their family members as well [ 18 ]. Female decision-making power at the group level had a beneficial effect on lowering the risk of anemia, implying that gender disparity, as measured by low decision-making power, may influence the development of anemia among married women.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that the decision-making capabilities of women in a society might have also an effect on their health and health-related behavior, more than the effect of individual women’s autonomy for two major reasons [ 18 ]. The first reason is that the presence of high numbers of a greater proportion of empowered women in a community could contribute to the information distribution related to better health outcomes to those with lower autonomous levels through formal and informal social networks [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in four countries, namely Namibia, Kenya, Nepal, and India, revealed that opposing attitudes toward wife beating measured at the community level affected maternal reproductive healthcare service utilization [ 40 ]. In 2014, Ebot et al also reported a strong association of community-level women’s autonomy on healthcare service utilization and indicated that the preventative healthcare service utilization of Ethiopian women with low individual-level autonomy was significantly increased if they lived in a community with a high level of women’s autonomy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study in Ethiopia showed that community-level factors were associated with the number of childhood immunizations, net of individual-level covariates. Children who lived in communities with high average education had almost 20% more immunizations compared with children from communities with low education ( 36 ). A study in Malawi found that regions with a high percentage of deliveries attended by health personnel were also characterized by a higher coverage of vaccination ( 37 ).…”
Section: Discussionmentioning
confidence: 99%